Isolation of a Low-Coordinate Rhodium Phosphine Complex Formed by C-C Bond Activation of Biphenylene - Chaplin, AB; Tonner, R; Weller, A (2010)
The isolation of a low-coordinate rhodium complex containing the 2,2′-biphenyl ligand, trans-[Rh(2,2′-biphenyl)(P iPr 3) 2][BAr F4], is described. This complex is prepared by C-C bond activation of biphenylene by the [Rh(P iPr 3) 2] + fragment and proceeds via the (isolated) intermediate π complex [Rh(η 6-biphenylene) (P iPr 3) 2][BAr F4]. An intramolecular ring slippage mechanism is suggested for this process, and this is supported by DFT calculations. © 2010 American Chemical Society.